Perancangan Vısual Rebrandıng Pada Bısnıs Kulıner Untuk Memperkenalkan Kota Batam dı Rıztour - Deli Deli; Jhon Carlie (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Riztour is a travel tour agency company that serves Southeast Asian travel to 3 destination countries, namely Singapore, Malaysia and Thailand. Riztour has provided various types of travel tour packages, but to be able to continue the travel tour business during the covid pandemic, Riztour needs a culinary rebranding video. The rebranding video will be made with the Adobe Premiere Pro CC 2019 and Adobe Photoshop CC 2019 applications, along with providing two types of subtitle languages, namely Indonesian and English along with background music. Data and information will be collected through observation and documentation. Riztour will upload this culinary rebranding video to his Youtube channel. The culinary rebranding video made by the author is expected to provide correct, precise and useful information to promote the Batam culinary business and increase the number of tourists who will visit Batam